A positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater and its preparation method

By introducing ultrasonic-assisted tannin modified multi-wall carbon nanotubes on the nanofiltration membrane, the interface polymerization reaction is regulated, and the problem of difficulty in simultaneously increasing the retention rate and water flux of the positive-electric nanofiltration membrane in the prior art is solved. A nanofiltration membrane was prepared that efficiently removes uranium and samarium from radioactive wastewater, achieving efficient treatment effect.

CN118976387BActive Publication Date: 2025-02-11CHINA AGRI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411252484.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-02-11
Estimated Expiration
2044-09-09

AI Technical Summary

Technical Problem

In the prior art, when treating radioactive wastewater, the retention rate and water flux of the positively charged nanofiltration membrane are difficult to increase at the same time, resulting in poor treatment effect.

Method used

By using interfacial polymerization method on the ultrafiltration bottom membrane, ultrasonic-assisted tannin modified multi-wall carbon nanotubes are introduced to regulate the interfacial polymerization process, thinning the thickness of the separation layer, improving the hydrophilicity of the membrane surface, and preparing efficient removal Positive charged nanofiltration membrane of uranium and samarium in radioactive wastewater.

Benefits of technology

It achieves the improvement of the water flux of the nanofiltration membrane while ensuring high interception. It is suitable for radioactive wastewater treatment and has broad prospects.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of nanofiltration membrane materials, and specifically relates to a method for preparing a positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater. According to the Donnan charge effect of the nanofiltration membrane, a positively charged branched polyaziridine is used as an aqueous phase monomer, and trimesoyl chloride is used as an organic phase monomer, and an interfacial polymerization method is adopted to prepare the positively charged nanofiltration membrane. Then, multi-walled carbon nanotubes are modified by ultrasound-assisted tannic acid, and tannic acid rich in hydrophilic OH can be wrapped on the surface of multi-walled carbon nanotubes, thereby improving the dispersibility and hydrophilicity of multi-walled carbon nanotubes in water, and adding the multi-walled carbon nanotubes to an aqueous phase solution, and the interfacial polymerization reaction process is regulated by using the unique nanopores and rich oxygen-containing functional groups of the tannic acid-modified multi-walled carbon nanotubes, the thickness of the separation layer is reduced, the roughness of the membrane surface is reduced, and the hydrophilicity of the membrane surface is improved, thereby improving the water flux and the retention rate of the positively charged nanofiltration membrane, and preparing a high-throughput positively charged nanofiltration membrane suitable for radioactive wastewater treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nanofiltration membrane materials, and specifically relates to a positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater and a preparation method thereof. Background Art

[0002] During the treatment of nuclear waste and the service of nuclear power plants, low- to medium-range radioactive wastewater containing radionuclides such as uranium, samarium, and cesium will be produced. This type of wastewater poses a huge threat to the natural environment and human health. Membrane separation technology is one of the core technologies in the field of radioactive wastewater treatment. Nanofiltration is a new type of membrane separation technology between ultrafiltration and reverse osmosis, with the advantages of excellent monovalent / polyvalent salt selectivity, simple operation, and low energy consumption. At present, there are two main mechanisms for the removal of pollutants by nanofiltration membranes, namely, size screening and Donnan charge effect. Size screening refers to the fact that pollutants with a size or molecular weight larger than the membrane pore size or molecular weight cutoff will be retained by the nanofiltration membrane, otherwise they will pass through; Donnan charge effect refers to the electrostatic interaction between the charge carried by the pollutant and the charge carried on the surface of the nanofiltration membrane, that is, charges of the same kind repel each other and charges of different kinds attract each other.

[0003] According to the type of charge on the surface of the nanofiltration membrane, the nanofiltration membrane can be divided into positively charged, neutrally charged and negatively charged nanofiltration membranes. Since radionuclides such as uranium and samarium in radioactive wastewater are mainly positively charged, and most of the commercial nanofiltration membranes on the market are negatively charged nanofiltration membranes, in the actual treatment of radioactive wastewater, the nuclides are easily adsorbed on the surface of the nanofiltration membrane, resulting in poor retention effect. Existing studies have shown that based on the positively charged characteristics of radionuclides, the removal effect of radionuclides by nanofiltration membranes can be effectively improved by preparing positively charged nanofiltration membranes, which has broad prospects in the treatment of radioactive wastewater.

[0004] However, there are few membranes for radioactive wastewater treatment at present. The positively charged nanofiltration membranes prepared by existing technologies still generally have the disadvantages of low rejection rate and low water flux, making it difficult to achieve simultaneous improvement of rejection rate and water flux. Therefore, it is of great practical significance to develop a new type of positively charged nanofiltration membrane material with high rejection and high flux suitable for radioactive wastewater treatment. Summary of the invention

[0005] The purpose of the present invention is to provide a positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater and a preparation method thereof. An interfacial polymerization method is adopted on an ultrafiltration bottom membrane to introduce multi-walled carbon nanotubes modified with tannic acid with good dispersibility into a polyamide layer, and the unique nanopores and rich oxygen-containing functional groups of the multi-walled carbon nanotubes modified with tannic acid are utilized to regulate the interfacial polymerization reaction process, reduce the thickness of the separation layer, reduce the roughness of the membrane surface, and improve the hydrophilicity of the membrane surface, so as to prepare a positively charged nanofiltration membrane suitable for radioactive wastewater treatment, which has a high water flux while ensuring a high retention rate for uranium and samarium.

[0006] The technical solution adopted by the present invention is as follows:

[0007] A method for preparing a positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater, the preparation method comprising the following steps:

[0008] S1: pre-treating the ultrafiltration bottom membrane to obtain a pre-treated ultrafiltration bottom membrane;

[0009] Wherein, the ultrafiltration bottom membrane pretreatment includes membrane synthesis, and the membrane synthesis adopts the following contents:

[0010] First, the membrane substrate is immersed in a solvent for preparing a membrane-forming solution or a colloid material, and the membrane solution or the colloid material is completely dissolved by heating;

[0011] Then, a positively charged modifier is added to the membrane solution or the colloidal material, wherein the modifier is any one of a quaternary ammonium salt or an ammonium salt;

[0012] The membrane solution or colloidal material is coated onto the support membrane by gel phase separation or phase transition method, and then dried and solidified to form the base material of the ultrafiltration bottom membrane;

[0013] S2: after mixing the branched polyaziridine and deionized water, performing a first stirring to obtain a branched polyaziridine aqueous solution;

[0014] S3: mixing tannic acid, multi-walled carbon nanotubes and deionized water, and then performing ultrasonic treatment to obtain a tannic acid-modified multi-walled carbon nanotube solution;

[0015] S4: mixing the branched polyaziridine aqueous solution in S2 and the tannic acid-modified multi-walled carbon nanotube solution in S3, and performing a second stirring to obtain an aqueous phase solution;

[0016] S5: After the trimesoyl chloride and the organic solvent are mixed, a third stirring is performed to obtain an organic phase solution;

[0017] S6: immersing the ultrafiltration bottom membrane pretreated by S1 into the aqueous solution in S4, then taking out the immersed ultrafiltration bottom membrane and rolling the surface solution with a rubber roller, and then immersing it into the organic solution in S5 to perform an interfacial polymerization reaction, thereby obtaining an ultrafiltration bottom membrane after interfacial polymerization;

[0018] S7: The ultrafiltration bottom membrane after interfacial polymerization in S6 is placed in an oven for heat treatment and cooling in sequence to obtain a positively charged nanofiltration membrane that can efficiently remove uranium and samarium from radioactive wastewater, and the performance of the positively charged nanofiltration membrane is evaluated.

[0019] Performance evaluation of positively charged nanofiltration membranes includes charge characteristic testing and filtration performance testing;

[0020] The charge characteristic test adopts the Zeta potential test method to test the membrane charge characteristic;

[0021] The filtration performance test includes a permeation flux test and a separation performance test.

[0022] In S1, the material of the ultrafiltration bottom membrane is any one of polysulfone and polyethersulfone, and the molecular weight cutoff of the ultrafiltration bottom membrane is 50-150KDa;

[0023] The pretreatment is as follows: immersing the ultrafiltration bottom membrane in deionized water at 10-30° C. for 48-72 hours, and replacing the deionized water every 12-24 hours.

[0024] In the S2, the first stirring time is 60-120 min, the first stirring temperature is 10-30° C., and the first stirring speed is 800-1500 rpm; and the concentration of the branched polyaziridine in the S2 is 0.1-3.0 wt %.

[0025] In the S3, the concentration of tannic acid is 0.01-0.05wt%, the concentration of multi-walled carbon nanotubes is 0.05-0.30wt%, and the conditions of the ultrasonic treatment are: ultrasonic time is 60-120min, and ultrasonic frequency is 20-40KHz.

[0026] In S4, the second stirring time is 60-120 min, the second stirring temperature is 10-30° C., and the second stirring speed is 800-1500 rpm;

[0027] The concentration of tannic acid modified multi-walled carbon nanotubes in the aqueous solution is 50-500 mg / L, and the concentration of branched polyaziridine is 0.1-3.0 wt %.

[0028] In S5, the third stirring time is 30-60 min, the third stirring temperature is 10-30° C., and the third stirring speed is 800-1500 rpm;

[0029] The concentration of trimesoyl chloride in the organic phase solution is 0.01-0.30 wt %.

[0030] In S6, the pretreated ultrafiltration bottom membrane is immersed in the aqueous solution for 1-10 minutes, then the immersed ultrafiltration bottom membrane is taken out and the surface solution is rolled dry with a rubber roller, and then immersed in the organic solution for 0.5-5 minutes to perform interfacial polymerization reaction, and the temperature of the interfacial polymerization reaction is room temperature.

[0031] In S7, the temperature of the heat treatment is 50-100° C., and the time of the heat treatment is 0.5-5 min.

[0032] The technical effects achieved by the present invention are:

[0033] The invention uses an ultrafiltration bottom membrane as a support layer, positively charged branched polyaziridine as a water phase monomer, trimesoyl chloride as an organic phase monomer, and adopts an interfacial polymerization method to prepare a positively charged nanofiltration membrane. On this basis, in order to further improve the water flux and retention rate of the nanofiltration membrane, multi-walled carbon nanotubes modified with tannic acid by ultrasound are added to the aqueous phase solution, and the ultrafiltration bottom membrane is immersed in the aqueous phase solution, so that the aqueous phase solution containing branched polyaziridine and tannic acid modified multi-walled carbon nanotubes are fully in contact with the ultrafiltration bottom membrane and adsorbed on the surface of the ultrafiltration bottom membrane, and then the immersed ultrafiltration bottom membrane is taken out and the surface solution is rolled dry with a rubber roller to remove the aqueous phase solution remaining on the membrane surface, and then immersed in the organic phase solution, so that the branched polyaziridine and tannic acid modified multi-walled carbon nanotubes adsorbed on the surface of the ultrafiltration bottom membrane are fully in contact with the trimesoyl chloride monomer in the organic phase solution and an interfacial polymerization reaction occurs at the interface between the two phases, forming a polyamide layer on the ultrafiltration bottom membrane, and then through heat treatment, the formed polyamide layer is further cross-linked and solidified, and its density and stability are improved, and after cooling, a positively charged nanofiltration membrane for efficiently removing uranium and samarium in radioactive wastewater is obtained.

[0034] The present invention modifies multi-walled carbon nanotubes with tannic acid through ultrasound, and tannic acid rich in hydrophilic -OH can be wrapped on the surface of multi-walled carbon nanotubes to improve the dispersibility and hydrophilicity of multi-walled carbon nanotubes in aqueous solution; by introducing multi-walled carbon nanotubes modified with tannic acid into a polyamide layer, the interfacial polymerization reaction process is regulated by using the unique nanopores and rich hydrophilic oxygen-containing functional groups (such as -OH, -COOH, -NH2, -SO3H) of the multi-walled carbon nanotubes modified with tannic acid, the thickness of the separation layer is reduced, the roughness of the membrane surface is reduced, the hydrophilicity of the membrane surface is improved, and the water flux and interception rate of the positively charged nanofiltration membrane are further improved, so as to prepare a high-throughput positively charged nanofiltration membrane suitable for radioactive wastewater treatment. The membrane is used for the treatment of radioactive wastewater containing uranium and samarium, and has a high interception rate for uranium and samarium ions while maintaining a high flux. DETAILED DESCRIPTION

[0035] In order to make the purpose and advantages of the present invention more clearly understood, the present invention is specifically described below in conjunction with embodiments. It should be understood that the following text is only used to describe one or several specific embodiments of the present invention, and does not strictly limit the scope of protection of the specific claims of the present invention.

[0036] A method for preparing a positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater, the preparation method comprising the following steps:

[0037] S1: pre-treating the ultrafiltration bottom membrane to obtain a pre-treated ultrafiltration bottom membrane;

[0038] Wherein, the ultrafiltration bottom membrane pretreatment includes membrane synthesis, and the membrane synthesis adopts the following contents:

[0039] First, the membrane substrate is immersed in a solvent for preparing a membrane-forming solution or a colloid material, and the membrane solution or the colloid material is completely dissolved by heating;

[0040] Then, a positively charged modifier is added to the membrane solution or the colloidal material, wherein the modifier is any one of a quaternary ammonium salt or an ammonium salt;

[0041] The membrane solution or colloidal material is coated onto the support membrane by gel phase separation or phase transition method, and then dried and solidified to form the base material of the ultrafiltration bottom membrane;

[0042] S2: After mixing the branched polyaziridine and deionized water, a first stirring is performed to obtain a branched polyaziridine aqueous solution; the relative molecular mass of the branched polyaziridine is preferably 500-10000, and more preferably 800. The present invention controls the relative molecular mass of the branched polyaziridine within the above range to ensure that the surface of the prepared positively charged nanofiltration membrane has abundant wrinkles and a suitable degree of crosslinking, which is beneficial to improving the water flux of the positively charged nanofiltration membrane and the retention rate of radionuclide ions.

[0043] S3: mixing tannic acid, multi-walled carbon nanotubes and deionized water, and then performing ultrasonic treatment to obtain a tannic acid-modified multi-walled carbon nanotube solution;

[0044] S4: mixing the branched polyaziridine aqueous solution in S2 and the tannic acid-modified multi-walled carbon nanotube solution in S3, and performing a second stirring to obtain an aqueous phase solution;

[0045] S5: After the trimesoyl chloride and the organic solvent are mixed, a third stirring is performed to obtain an organic phase solution; the organic solvent is preferably any one or a combination of at least two of n-hexane, cyclohexane, n-heptane and Isopar L isoparaffin, more preferably n-hexane;

[0046] Among them, S4 and S5 have no order of precedence;

[0047] S6: immersing the ultrafiltration bottom membrane pretreated by S1 into the aqueous solution in S4, then taking out the immersed ultrafiltration bottom membrane and rolling the surface solution with a rubber roller, and then immersing it into the organic solution in S5 to perform an interfacial polymerization reaction, thereby obtaining an ultrafiltration bottom membrane after interfacial polymerization;

[0048] S7: The ultrafiltration bottom membrane after the interfacial polymerization in S6 is placed in an oven for heat treatment and cooling in sequence to obtain a positively charged nanofiltration membrane for removing uranium and samarium from radioactive wastewater, and the performance of the positively charged nanofiltration membrane is evaluated.

[0049] Performance evaluation of positively charged nanofiltration membranes includes charge characteristic testing and filtration performance testing;

[0050] The charge characteristic test adopts the Zeta potential test method to test the membrane charge characteristic;

[0051] The filtration performance test includes a permeation flux test and a separation performance test; the permeation flux of the membrane is tested to ensure its filtration capacity; and the separation performance test is performed using a model solution containing uranium and samarium to evaluate its removal efficiency and selectivity.

[0052] In S1, the material of the ultrafiltration bottom membrane is any one of polysulfone and polyethersulfone, and the molecular weight cutoff of the ultrafiltration bottom membrane is 50-150KDa; the molecular weight cutoff of the ultrafiltration bottom membrane is controlled within the above range so that the ultrafiltration bottom membrane has sufficient porosity and appropriate pore size, which is beneficial to improve the retention rate of the subsequently prepared positively charged nanofiltration membrane for nuclides (such as uranium and samarium).

[0053] Pretreatment is: immerse the ultrafiltration bottom membrane in deionized water at 10-30°C for 48-72 hours, and replace the deionized water every 12-24 hours. Pretreatment is used to remove impurities on the surface of the ultrafiltration bottom membrane and make it fully wet, which is conducive to the subsequent interfacial polymerization reaction.

[0054] In S2, the first stirring time is 60-120 min, the first stirring temperature is 10-30° C., and the first stirring speed is 800-1500 rpm. Through the first stirring, a branched polyaziridine solution with good dispersibility is obtained.

[0055] The concentration of branched polyaziridine in S2 is 0.1-3.0 wt %, more preferably 1.0-2.0 wt %. The present invention controls the concentration of branched polyaziridine within the above range to ensure the formation of a dense polyamide separation layer, thereby preparing a positively charged nanofiltration membrane with better performance.

[0056] In S3, the concentration of tannic acid is 0.01-0.05wt%, and the concentration of tannic acid is controlled within the above range to ensure that the tannic acid is fully in contact with the multi-walled carbon nanotubes and wrapped on the surface of the multi-walled carbon nanotubes, thereby improving the dispersibility and hydrophilicity of the multi-walled carbon nanotubes in the aqueous solution, and facilitating the formation of a uniform and defect-free polyamide separation layer; the multi-walled carbon nanotubes include one or more of multi-walled carbon nanotubes, hydroxylated multi-walled carbon nanotubes, carboxylated multi-walled carbon nanotubes, aminated multi-walled carbon nanotubes, and sulfonated multi-walled carbon nanotubes, and more preferably carboxylated multi-walled carbon nanotubes. Carbon nanotubes; the concentration of multi-walled carbon nanotubes is 0.05-0.30wt%, and the concentration of the multi-walled carbon nanotubes is controlled within the above range to facilitate the control of the addition amount while avoiding the problem of poor dispersibility caused by excessive concentration of the multi-walled carbon nanotubes; the conditions for ultrasonic treatment are: ultrasonic time 60-120min, ultrasonic frequency 20-40KHz, and by controlling the ultrasonic time and frequency within the above range to improve the dispersibility of the multi-walled carbon nanotubes, it is beneficial for the subsequent multi-walled carbon nanotubes to be uniformly dispersed in the prepared positively charged nanofiltration membrane.

[0057] In S4, the second stirring time is 60-120 min, the second stirring temperature is 10-30° C., and the second stirring speed is 800-1500 rpm. Through the second stirring, an aqueous solution containing branched polyaziridine and tannic acid-modified multi-walled carbon nanotubes with good dispersion is obtained.

[0058] The concentration of tannic acid modified multi-walled carbon nanotubes in the aqueous solution is 50-500 mg / L, more preferably 100-300 mg / L; the concentration of branched polyaziridine is 0.1-3.0 wt %, more preferably 1.0-2.0 wt %; by controlling the concentrations of tannic acid modified multi-walled carbon nanotubes and branched polyaziridine within the above ranges, a dense polyamide separation layer is formed, and the tannic acid modified multi-walled carbon nanotubes are uniformly distributed in the polyamide layer, thereby preparing a positively charged nanofiltration membrane with better performance.

[0059] In S5, the third stirring time is 30-60 min, the third stirring temperature is 10-30° C., and the third stirring speed is 800-1500 rpm; through the third stirring, an organic phase solution with good dispersibility is obtained.

[0060] The concentration of trimesoyl chloride in the organic phase solution is 0.01-0.30wt%. By controlling the concentration of trimesoyl chloride in the above range, a sufficient and appropriate amount of acyl chloride monomer is provided to react with the branched polyaziridine and tannic acid-modified multi-walled carbon nanotubes in the aqueous phase solution, so as to prepare a positively charged nanofiltration membrane with better performance.

[0061] In S6, the pre-treated ultrafiltration bottom membrane is immersed in the aqueous solution for 1-10 minutes, more preferably 2-6 minutes; the time for the ultrafiltration bottom membrane to be immersed in the aqueous solution is controlled within the above range, so that the aqueous solution is fully in contact with the ultrafiltration bottom membrane and adsorbed on the surface of the ultrafiltration bottom membrane, which is convenient for subsequent reactions; then the immersed ultrafiltration bottom membrane is taken out and the surface solution is rolled dry with a rubber roller, and then immersed in the organic phase solution for 0.5-5 minutes for interfacial polymerization reaction, more preferably 1-3 minutes; the temperature of the interfacial polymerization reaction is room temperature. By controlling the time and temperature of the interfacial polymerization reaction within the above range, the degree of the interfacial polymerization reaction is controlled, so that the prepared positively charged nanofiltration membrane has a higher water flux and retention rate.

[0062] In S7, the heat treatment temperature is 50-100°C, and the heat treatment time is 0.5-5 minutes. By controlling the heat treatment time and temperature within the above range, the formed polyamide layer is further cross-linked to form a stable polyamide layer.

[0063] In the present invention, the heat-treated membrane is taken out and naturally cooled to obtain a positively charged nanofiltration membrane that can efficiently remove uranium and samarium from radioactive wastewater. The membrane is preferably sealed in deionized water for more than 24 hours for standby use.

[0064] The method provided by the present invention uses a branched polyaziridine with a positive charge as an aqueous phase monomer, trimesoyl chloride as an organic phase monomer, and adds multi-walled carbon nanotubes modified with tannic acid with the aid of ultrasound to the aqueous phase solution, and the tannic acid rich in hydrophilic -OH can be wrapped on the surface of the multi-walled carbon nanotubes to improve the dispersibility and hydrophilicity of the multi-walled carbon nanotubes in the aqueous solution. By introducing the multi-walled carbon nanotubes modified with tannic acid into the polyamide layer, the interfacial polymerization reaction process is regulated by using the unique nanopores and rich hydrophilic oxygen-containing functional groups of the multi-walled carbon nanotubes modified with tannic acid, the thickness of the separation layer is reduced, the roughness of the membrane surface is reduced, and the hydrophilicity of the membrane surface is improved, so as to prepare a high-throughput positively charged nanofiltration membrane suitable for the treatment of radioactive wastewater. And the preparation method of the positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater provided by the present invention is simple to operate, has mild reaction conditions, and is suitable for large-scale production.

[0065] The present invention also provides a positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater, which is prepared by the preparation method described in the above technical solution.

[0066] A positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater is prepared by the preparation method.

[0067] Embodiment 1:

[0068] The preparation method of the positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater comprises the following steps (the following steps without temperature indication are all carried out at room temperature):

[0069] (1) Cut a polyethersulfone ultrafiltration membrane with a molecular weight cutoff of 100 KDa into a square of 7×7 cm, soak it in deionized water for 48 hours, and replace the deionized water every 12 hours to obtain a pretreated ultrafiltration bottom membrane;

[0070] (2) taking 2 g of branched polyethylenimine with a relative molecular mass of 800 into a beaker, adding 50 g of deionized water, placing it on a magnetic stirrer, and stirring it for 120 min at a speed of 1000 rpm to obtain a branched polyethylenimine aqueous solution with good dispersibility;

[0071] (3) Weigh 0.1 g of carboxylated multi-walled carbon nanotubes into a beaker, add 90 g of deionized water, and then add 10 mL of a 24 mM tannic acid aqueous solution, and ultrasonicate for 120 min at a frequency of 30 kHz to obtain a tannic acid-modified carboxylated multi-walled carbon nanotube solution with good dispersion, wherein the concentration of the tannic acid-modified carboxylated multi-walled carbon nanotubes is 0.1 wt %;

[0072] (4) taking 5 mL of the tannic acid-modified carboxylated multi-walled carbon nanotube solution obtained in step (3), adding it to the branched polyaziridine aqueous solution obtained in step (2), and then adding deionized water to 100 g, placing it on a magnetic stirrer, and performing a second stirring at a speed of 1000 rpm for 120 min to obtain an aqueous phase solution with good dispersibility; wherein the concentration of the branched polyaziridine in the aqueous phase solution is 2 wt %, and the concentration of the tannic acid-modified carboxylated multi-walled carbon nanotube is 50 mg / L;

[0073] (5) 0.05 g of trimesoyl chloride was dissolved in 100 g of n-hexane solvent, and the mixture was stirred for 30 min at 1000 rpm to obtain a uniformly dispersed organic phase solution; wherein the concentration of trimesoyl chloride in the organic phase solution was 0.05 wt %;

[0074] (6) immersing the ultrafiltration bottom membrane pretreated in step (1) into the aqueous solution obtained in step (4) for 5 minutes, taking it out and drying the solution on the membrane surface with a rubber roller, and then immersing it into the organic solution obtained in step (5) for interfacial polymerization reaction for 1 minute to obtain an ultrafiltration bottom membrane after interfacial polymerization reaction;

[0075] (7) The ultrafiltration bottom membrane obtained after the interfacial polymerization reaction in the above step (6) is placed in an oven, heat treated at 60° C. for 1 min, taken out, cooled, and sealed in deionized water for more than 24 h for use, thereby obtaining a positively charged nanofiltration membrane that can efficiently remove uranium and samarium from radioactive wastewater.

[0076] At a pressure of 0.4 MPa, the performance of the positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater prepared in Example 1 was tested with 50 mg / L UO2(NO3)2 and 50 mg / L Sm(NO3)3, respectively. The test results showed that the pure water flux of the positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater prepared in Example 1 was 11.81 L·m -2 ·h -1 bar -1 , for UO2 2+ The interception rate of Sm 3+ The interception rate is 98.25%.

[0077] Example 2

[0078] A positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater was prepared according to the method of Example 1, except that in step (4), 10 mL of tannic acid-modified carboxylated multi-walled carbon nanotube solution was added to an aqueous solution containing branched polyaziridine; and the concentration of tannic acid-modified carboxylated multi-walled carbon nanotubes in the aqueous phase solution was 100 mg / L.

[0079] The same method as in Example 1 was used to test the performance of the positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater prepared in Example 2. The specific results are shown in Table 1.

[0080] Example 3

[0081] A positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater was prepared according to the method of Example 1, except that in step (4), 15 mL of tannic acid-modified carboxylated multi-walled carbon nanotube solution was added to an aqueous solution containing branched polyaziridine; and the concentration of tannic acid-modified carboxylated multi-walled carbon nanotubes in the aqueous phase solution was 150 mg / L.

[0082] The same method as in Example 1 was used to test the performance of the positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater prepared in Example 3. The specific results are shown in Table 1.

[0083] Example 4

[0084] A positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater was prepared according to the method of Example 1, except that in step (4), 20 mL of tannic acid-modified carboxylated multi-walled carbon nanotube solution was added to an aqueous solution containing branched polyaziridine; and the concentration of tannic acid-modified carboxylated multi-walled carbon nanotubes in the aqueous phase solution was 200 mg / L.

[0085] The same method as in Example 1 was used to test the performance of the positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater prepared in Example 4. The specific results are shown in Table 1.

[0086] Example 5

[0087] A positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater was prepared according to the method of Example 1, except that in step (4), 25 mL of tannic acid-modified carboxylated multi-walled carbon nanotube solution was added to an aqueous solution containing branched polyaziridine; and the concentration of tannic acid-modified carboxylated multi-walled carbon nanotubes in the aqueous phase solution was 250 mg / L.

[0088] The same method as in Example 1 was used to test the performance of the positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater prepared in Example 5. The specific results are shown in Table 1.

[0089] Example 6

[0090] A positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater was prepared according to the method of Example 1, except that in step (4), 30 mL of tannic acid-modified carboxylated multi-walled carbon nanotube solution was added to an aqueous solution containing branched polyaziridine; and the concentration of tannic acid-modified carboxylated multi-walled carbon nanotubes in the aqueous phase solution was 300 mg / L.

[0091] The same method as in Example 1 was used to test the performance of the positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater prepared in Example 6. The specific results are shown in Table 1.

[0092] Comparative Example 1

[0093] The preparation method of the positively charged nanofiltration membrane without introducing tannic acid-modified carboxylated multi-walled carbon nanotubes comprises the following steps (the following steps without indicating the temperature are all carried out at room temperature):

[0094] (1) Cut a polyethersulfone ultrafiltration membrane with a molecular weight cutoff of 100 KDa into a square of 7×7 cm, soak it in deionized water for 48 hours, and replace the deionized water every 12 hours to obtain a pretreated ultrafiltration bottom membrane;

[0095] (2) taking 2 g of branched polyethylenimine with a relative molecular mass of 800 into a beaker, adding deionized water to 100 g, placing the beaker on a magnetic stirrer, and performing a first stirring at a speed of 1000 rpm for 120 min to obtain an aqueous phase solution with good dispersibility; wherein the concentration of the branched polyethylenimine in the aqueous phase solution is 2 wt %;

[0096] (3) 0.025 g of trimesoyl chloride was dissolved in 100 g of n-hexane solvent, and the mixture was stirred for 30 min at 1000 rpm to obtain a uniformly dispersed organic phase solution; wherein the concentration of trimesoyl chloride in the organic phase solution was 0.025 wt %;

[0097] (4) immersing the ultrafiltration bottom membrane pretreated in the above step (1) into the aqueous solution obtained in step (2) for 5 minutes, taking it out and rolling the membrane surface solution dry with a rubber roller, and then immersing it in the organic solution obtained in step (3) for interfacial polymerization reaction for 1 minute to obtain an ultrafiltration bottom membrane after interfacial polymerization reaction;

[0098] (5) The ultrafiltration bottom membrane obtained after the interfacial polymerization reaction in the above step (4) is placed in an oven, heat-treated at 60° C. for 1 min, taken out, cooled, and sealed in deionized water for more than 24 h for use, thereby obtaining a positively charged nanofiltration membrane without the introduction of tannic acid-modified carboxylated multi-walled carbon nanotubes.

[0099] The same method as in Example 1 was used to test the performance of the positively charged nanofiltration membrane prepared in Comparative Example 1 without the introduction of tannic acid-modified carboxylated multi-walled carbon nanotubes. The specific results are shown in Table 1.

[0100] Comparative Example 2

[0101] A positively charged nanofiltration membrane without introducing tannic acid-modified carboxylated multi-walled carbon nanotubes was prepared according to the method of Comparative Example 1, except that in step (3), 0.05 g of trimesoyl chloride was dissolved in 100 g of n-hexane solvent; the concentration of trimesoyl chloride in the organic phase solution was 0.05 wt %;

[0102] The same method as that of Comparative Example 1 was used to test the performance of the positively charged nanofiltration membrane prepared in Comparative Example 2 without the introduction of tannic acid-modified carboxylated multi-walled carbon nanotubes. The specific results are shown in Table 1.

[0103] Comparative Example 3

[0104] A positively charged nanofiltration membrane without introducing tannic acid-modified carboxylated multi-walled carbon nanotubes was prepared according to the method of Comparative Example 1, except that in step (3), 0.10 g of trimesoyl chloride was dissolved in 100 g of n-hexane solvent; the concentration of trimesoyl chloride in the organic phase solution was 0.10 wt %;

[0105] The same method as that of Comparative Example 1 was used to test the performance of the positively charged nanofiltration membrane prepared in Comparative Example 3 without the introduction of tannic acid-modified carboxylated multi-walled carbon nanotubes. The specific results are shown in Table 1.

[0106] Comparative Example 4

[0107] A positively charged nanofiltration membrane without introducing tannic acid-modified carboxylated multi-walled carbon nanotubes was prepared according to the method of Comparative Example 1, except that in step (3), 0.15 g of trimesoyl chloride was dissolved in 100 g of n-hexane solvent; the concentration of trimesoyl chloride in the organic phase solution was 0.15 wt %;

[0108] The same method as that of Comparative Example 1 was used to test the performance of the positively charged nanofiltration membrane prepared in Comparative Example 4 without the introduction of tannic acid-modified carboxylated multi-walled carbon nanotubes. The specific results are shown in Table 1.

[0109] Comparative Example 5

[0110] A positively charged nanofiltration membrane without introducing tannic acid-modified carboxylated multi-walled carbon nanotubes was prepared according to the method of Comparative Example 1, except that in step (3), 0.20 g of trimesoyl chloride was dissolved in 100 g of n-hexane solvent; the concentration of trimesoyl chloride in the organic phase solution was 0.20 wt %;

[0111] The same method as that of Comparative Example 1 was used to test the performance of the positively charged nanofiltration membrane prepared in Comparative Example 5 without the introduction of tannic acid-modified carboxylated multi-walled carbon nanotubes. The specific results are shown in Table 1.

[0112] Comparative Example 6

[0113] A positively charged nanofiltration membrane without introducing tannic acid-modified carboxylated multi-walled carbon nanotubes was prepared according to the method of Comparative Example 1, except that in step (3), 0.25 g of trimesoyl chloride was dissolved in 100 g of n-hexane solvent; the concentration of trimesoyl chloride in the organic phase solution was 0.25 wt %;

[0114] The same method as that of Comparative Example 1 was used to test the performance of the positively charged nanofiltration membrane prepared in Comparative Example 6 without the introduction of tannic acid-modified carboxylated multi-walled carbon nanotubes. The specific results are shown in Table 1.

[0115] Table 1 Performance data of positively charged nanofiltration membranes for efficient removal of uranium and samarium from radioactive wastewater prepared in Examples 1-6 and positively charged nanofiltration membranes prepared in Comparative Examples 1-6 without introduction of tannic acid-modified carboxylated multi-walled carbon nanotubes

[0116] Example <![CDATA[Pure water flux (L·m -2 ·h -1 ·bar -1 )]]> <![CDATA[UO2 2+ Retention rate (%)]]> <![CDATA[Sm 3+ Retention rate (%)]]> Example 1 11.81 97.54 98.25 Example 2 12.52 97.88 98.29 Example 3 13.37 98.13 98.65 Example 4 13.15 97.84 98.32 Example 5 12.90 97.46 98.08 Example 6 12.35 97.33 97.85 Comparative Example 1 21.03 75.20 78.35 Comparative Example 2 13.90 93.55 94.37 Comparative Example 3 9.73 96.65 96.82 Comparative Example 4 6.85 97.22 97.68 Comparative Example 5 6.73 97.35 97.16 Comparative Example 6 6.83 96.39 97.05

[0117] In summary, the positively charged nanofiltration membranes prepared in Examples 1-6 of the present invention for efficiently removing uranium and samarium from radioactive wastewater have excellent overall performance and a pure water flux of up to 13.37 L·m -2 ·h -1 bar -1 , for UO2 2+ The interception rate of Sm 3+ The interception rate can reach 98.65%. The comprehensive performance of the positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater prepared in the embodiment of the present invention is generally higher than that of the positively charged nanofiltration membrane prepared in comparative examples 1-6 without introducing tannic acid-modified carboxylated multi-walled carbon nanotubes.

[0118] The above are only preferred embodiments of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made without departing from the principles of the present invention, and these improvements and modifications should also be considered as the protection scope of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention shall be implemented according to conventional means in the art unless otherwise specified and limited.

Claims

1. A method for preparing a positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater, characterized in that: The preparation method comprises the following steps: S1: pre-treating the ultrafiltration bottom membrane to obtain a pre-treated ultrafiltration bottom membrane; the ultrafiltration bottom membrane is made of any one of polysulfone and polyethersulfone; Wherein, the ultrafiltration bottom membrane pretreatment includes membrane synthesis, and the membrane synthesis adopts the following contents: First, the membrane substrate is immersed in a solvent for preparing a membrane-forming solution or a colloid material, and the membrane solution or the colloid material is completely dissolved by heating; Then, a positively charged modifier is added to the membrane solution or the colloidal material, wherein the modifier is any one of a quaternary ammonium salt or an ammonium salt; The membrane solution or colloidal material is coated onto the support membrane by gel phase separation or phase transition method, and then dried and solidified to form the base material of the ultrafiltration bottom membrane; S2: after mixing the branched polyaziridine and deionized water, performing a first stirring to obtain a branched polyaziridine aqueous solution; In the S2, the first stirring time is 60-120 min, the first stirring temperature is 10-30° C., and the first stirring speed is 800-1500 rpm; the concentration of the branched polyaziridine in the S2 is 0.1-3.0 wt %; S3: mixing tannic acid, multi-walled carbon nanotubes and deionized water, and then subjecting the mixture to ultrasonic treatment to obtain a tannic acid-modified multi-walled carbon nanotube solution; the concentration of tannic acid is 0.01-0.05wt%, and the concentration of multi-walled carbon nanotubes is 0.05-0.30wt%; S4: after mixing the branched polyaziridine aqueous solution in S2 and the tannic acid modified multi-walled carbon nanotube solution in S3, performing a second stirring to obtain an aqueous phase solution; the second stirring time is 60-120 min, the second stirring temperature is 10-30° C., and the second stirring speed is 800-1500 rpm; S5: After the trimesoyl chloride and the organic solvent are mixed, a third stirring is performed to obtain an organic phase solution; the third stirring time is 30-60 min, the third stirring temperature is 10-30° C., and the third stirring speed is 800-1500 rpm; S6: immersing the ultrafiltration bottom membrane pretreated by S1 into the aqueous solution in S4, then taking out the immersed ultrafiltration bottom membrane and rolling the surface solution with a rubber roller, and then immersing it into the organic solution in S5 to perform an interfacial polymerization reaction, thereby obtaining an ultrafiltration bottom membrane after interfacial polymerization; S7: The ultrafiltration bottom membrane after the interfacial polymerization in S6 is placed in an oven for heat treatment and cooling in sequence to obtain a positively charged nanofiltration membrane for removing uranium and samarium from radioactive wastewater, and the performance of the positively charged nanofiltration membrane is evaluated.

2. The method for preparing a positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater according to claim 1, characterized in that: In S1, the molecular weight cutoff of the ultrafiltration bottom membrane is 50-150KDa; The pretreatment is as follows: immersing the ultrafiltration bottom membrane in deionized water at 10-30° C. for 48-72 hours, and replacing the deionized water every 12-24 hours.

3. The method for preparing a positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater according to claim 1, characterized in that: In S3, the conditions of the ultrasonic treatment are: ultrasonic time 60-120 min, ultrasonic frequency 20-40 KHz.

4. The method for preparing a positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater according to claim 1, characterized in that: In the step S4, the concentration of tannic acid-modified multi-walled carbon nanotubes in the aqueous solution is 50-500 mg / L, and the concentration of branched polyaziridine is 0.1-3.0 wt %.

5. The method for preparing a positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater according to claim 1, characterized in that: In S5, the concentration of trimesoyl chloride in the organic phase solution is 0.01-0.30 wt %.

6. The method for preparing a positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater according to claim 1, characterized in that: In S6, the pretreated ultrafiltration bottom membrane is immersed in the aqueous solution for 1-10 minutes, then the immersed ultrafiltration bottom membrane is taken out and the surface solution is rolled dry with a rubber roller, and then immersed in the organic solution for 0.5-5 minutes to perform interfacial polymerization reaction, and the temperature of the interfacial polymerization reaction is room temperature.

7. The method for preparing a positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater according to claim 1, characterized in that: In S7, the temperature of the heat treatment is 50-100° C., and the time of the heat treatment is 0.5-5 min.

8. The method for preparing a positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater according to claim 1, characterized in that: In S7, the performance evaluation of the positively charged nanofiltration membrane includes a charge characteristic test and a filtration performance test; The charge characteristic test adopts the Zeta potential test method to test the membrane charge characteristic; The filtration performance test includes a permeation flux test and a separation performance test.

9. A positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater, characterized in that: A positively charged nanofiltration membrane for efficiently removing uranium and samarium from radioactive wastewater is prepared by the preparation method described in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Method for efficiently recovering gold based on polytannic acid coated carbon nanotube composite membrane

    CN113684371A

  • Positively charged nanofiltration membrane for removing uranium and cesium in nuclear radioactive wastewater and preparation method of positively charged nanofiltration membrane

    CN116531961A